1989
DOI: 10.1177/172460088900400306
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Composite Laboratory Tests in the Diagnosis of Liver Malignancies

Abstract: The utility of the markers CEA, beta-HCG, CA-50, alpha-fetoprotein (APF), ferritin, alkaline phosphatase (AP), its isoenzyme liver-1 (APL1), gamma-glutamyltransferase (gGT), its fast migrating isoenzyme (gGT1) and 5'nucleotidase (5'N) in differentiating liver malignancies and benign involvement was evaluated in the sera of 85 patients with hepatocellular carcinoma (HCC), 157 with chronic liver disease (CLD) and 91 with liver metastases (LM) derived from different tumors. The mean concentrations of all the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…S4), which is also consistent with the activation of a DNA damage response (Rokhlin et al, 2008). In addition, hepatocellular carcinoma (HCC) progression markers, such as gamma-glutamyl transpeptidase 1 (Pavesi et al, 1989) and insulin-like growth factor II (Qiu et al, 2008) were up-regulated in the microarray analysis of Alb-Cre:Hdac3 −/− livers by 2.2- and 2.7-fold respectively (Knutson et al, 2008). These data, coupled with the observed genomic instability, prompted us to age cohorts of 20 control and 20 Alb-Cre:Hdac3 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…S4), which is also consistent with the activation of a DNA damage response (Rokhlin et al, 2008). In addition, hepatocellular carcinoma (HCC) progression markers, such as gamma-glutamyl transpeptidase 1 (Pavesi et al, 1989) and insulin-like growth factor II (Qiu et al, 2008) were up-regulated in the microarray analysis of Alb-Cre:Hdac3 −/− livers by 2.2- and 2.7-fold respectively (Knutson et al, 2008). These data, coupled with the observed genomic instability, prompted us to age cohorts of 20 control and 20 Alb-Cre:Hdac3 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…In this study it was observed that GGT1 was significantly expressed in breast cancer when compared with the control. The expression of tumor tissue GGT1 has also been shown in various cancers such as prostate (Kawakami et al 2017), epithelial (Lukic et al 2016), lung (Hino et al 2016), colorectal (Palaniappan et al 2016), overian (Mahata 2006), liver (Pavesi et al 1989), and breast (Banneau et al 2010).…”
Section: Discussionmentioning
confidence: 97%